Copper-Catalyzed Aerobic Oxidative C–C Bond Cleavage of 1,3-Diaryldiketones To Synthesize 1,2-Diketones - Zhang, Chun; Wang, Xiaoyang; Jiao, Ning (Synlett, 2014)
An aerobic oxidative C–C bond cleavage of 1,3-diaryldiketones for the synthesis of 1,2-diketones by using O2 as the oxidant has been developed. Control experiments illustrate that the copper catalyst not only assist the aerobic oxidative process of 1,3-diketones, but also catalyze the 1,2-Wagner–Meerwein-type rearrangement process.
Keywords: copper; C–C bond cleavage; aerobic oxidative reaction; 1,2-diketones